Aplicação do método AHP no processo de seleção de fornecedores em um empreendimento de Cerro Corá/RN - Costa Neto, Leon Antônio (Universidade Federal Rural do Semi-Árido, 2020)
This study seeks to establish the ranking of suppliers of refrigeration products for a project in the city of Cerro Corá / RN. The model applied for selection of suppliers was the AHP (Analytic Hierarchy Process). To this end, a case study was carried out, of an applied nature, a combined approach and descriptive and exploratory objectives, seeking information on company characteristics, as well as definition of the evaluation criteria of the suppliers, and then the AHP method was applied. The company analyzed the performance requirements to define the supplier, such as quality, speed, cost, reliability and flexibility, classifying these characteristics as essential so that it can offer its customers products that meet their expectations and subcriteria that have the potential to be used in the selection of suppliers. It was concluded that the best option, among the analyzed suppliers, is Supplier 1 located in Sousa / PB. As a second option, Supplier 3 located in Caicó / RN. It should be noted that the final decision on purchasing material from these suppliers will be the manager.
Monografia
Keywords: Método multicritério; Tomada de decisão; Objetivos de desempenho; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA